Determinants of sustainable solid waste management in Jimma City, Southwest Ethiopia - Gutama Haile Degefa; Kasahun Eba; Habtamu Roba; Mohammedgezali Ibrahim; Zewdie Birhanu; Temima Jemal; Worku Jimma; Fikadu Mitiku; Gudina Terefe Tucho (PLoS ONE, 2025)
Background Exponential urban growth has led to a significant increase in solid waste production, making solid waste one of the most significant issues faced by urban spaces in developing countries. This rising volume of solid waste has led to pressing public health and environmental concerns, such as water, soil, and air pollution, increased greenhouse gas emissions, and the spread of diseases. Thus, this study aimed to evaluate the sustainable solid waste management practices and challenges in Jimma City, southwestern Ethiopia. Methods A community-based cross-sectional study design was employed in this study. Quantitative data and solid waste samples were collected between 01/01/2024 and 01/03/2024 via stratified random sampling from 820 participants in Jimma City, Southwest Ethiopia. The data was analyzed using STATA 18, and a p-value <0.05 was used to determine the level of statistical significance. Results This study revealed a solid waste generation rate of 0.66 Kg/capita/day and the majority of households (84.63%) do not segregate their solid waste at a point of generation; only 38.66% of Households had access to door-to-door solid waste collection services even though about 81.71% of households are willing to pay for solid waste collection services and 69.76% of Households dump waste along rivers or roadsides. Household income, geographic location, level of education, and attitude are the major determinants of sustainable solid waste management, with Average Marginal Effects of (0.0411, 0.1098, 0.0621, 0.0495), respectively. Conclusion There is a higher rate of solid waste generation and a lack of integrated solid waste management services like door-to-door collection, temporary public solid waste collection containers, and disposal systems. This study indicated that about 2/3 of total solid waste generation is attributed to organic waste, and limited waste-to-resource recovery practices are observed. Thus, systematic provisions of integrated solid waste management services, implementation of solid waste reduction, and waste-to-resource recovery strategies focusing on composting are recommended.